Mutations in DNAJC19 cause altered mitochondrial structure and increased mitochondrial respiration in human iPSC-derived cardiomyocytes - Anna Janz; Katharina Walz; Alexandra Cirnu; Jessica Surjanto; Daniela Urlaub; Miriam Leskien; Michael Kohlhaas; Alexander Nickel; Theresa Brand; Naoko Nose; Philipp Wörsdörfer; Nicole Wagner; et al. (Elsevier, 2024)
Background: Dilated cardiomyopathy with ataxia (DCMA) is an autosomal recessive disorder arising from truncating mutations in DNAJC19, which encodes an inner mitochondrial membrane protein. Clinical features include an early onset, often life-threatening, cardiomyopathy associated with other metabolic features. Here, we aim to understand the metabolic and pathophysiological mechanisms of mutant DNAJC19 for the development of cardiomyopathy. Methods: We generated induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) of two affected siblings with DCMA and a gene-edited truncation variant (tv) of DNAJC19 which all lack the conserved DnaJ interaction domain. The mutant iPSC-CMs and their respective control cells were subjected to various analyses, including assessments of morphology, metabolic function, and physiological consequences such as Ca2+ kinetics, contractility, and arrhythmic potential. Validation of respiration analysis was done in a gene-edited HeLa cell line (DNAJC19tvHeLa). Results: Structural analyses revealed mitochondrial fragmentation and abnormal cristae formation associated with an overall reduced mitochondrial protein expression in mutant iPSC-CMs. Morphological alterations were associated with higher oxygen consumption rates (OCRs) in all three mutant iPSC-CMs, indicating higher electron transport chain activity to meet cellular ATP demands. Additionally, increased extracellular acidification rates suggested an increase in overall metabolic flux, while radioactive tracer uptake studies revealed decreased fatty acid uptake and utilization of glucose. Mutant iPSC-CMs also showed increased reactive oxygen species (ROS) and an elevated mitochondrial membrane potential. Increased mitochondrial respiration with pyruvate and malate as substrates was observed in mutant DNAJC19tv HeLa cells in addition to an upregulation of respiratory chain complexes, while cellular ATP-levels remain the same. Moreover, mitochondrial alterations were associated with increased beating frequencies, elevated diastolic Ca2+ concentrations, reduced sarcomere shortening and an increased beat-to-beat rate variability in mutant cell lines in response to β-adrenergic stimulation. Conclusions: Loss of the DnaJ domain disturbs cardiac mitochondrial structure with abnormal cristae formation and leads to mitochondrial dysfunction, suggesting that DNAJC19 plays an essential role in mitochondrial morphogenesis and biogenesis. Moreover, increased mitochondrial respiration, altered substrate utilization, increased ROS production and abnormal Ca2+ kinetics provide insights into the pathogenesis of DCMA-related cardiomyopathy.